Oral History Program Interview: Viola Lillian Maxwell Mitchell - Mitchell, Viola Lillian Maxwell
Mitchell was born in Spiro, Oklahoma in 1912. She and her husband came to Bakersfield, California on April 16, 1935. This interview contains descriptions of dust storms, Mitchell's charitable nature towards other migrants in need, the forms of recreational activities women participated in, what motherhood was like for female migrants, negative perceptions of taking charity and welfare users, examples of discrimination aimed at "Okies," and the dire straits of ditch camp life.